SLOW DEFORMATION WAVES IN THE SEISMIC REGIME AND GEOPHYSICAL FIELDS AT THE NORTHERN MARGIN OF THE AMUR PLATE - S. V. Trofimenko; V. G. Bykov; N. N. Grib (Геодинамика и тектонофизика)
The interaction between the Amur, Pacific and Eurasian tectonic plates initiates seismic activity at the plate margins as well as in the plate periphery, as evidenced by intracontinental earthquakes. In the Amur plate, the dynamics of intercontinental seismicity is controlled by deformation wave fronts comprising a regular pattern of equidistant zones [Sherman, 2013]. According to [Trofimenko et al., 2015a, 2015b, 2016], maximum values of seismic activity in the range of magnitudes 2≤M≤4 also form a sequence of spatial cells in the form of seismic clusters from the east (Sakhalin – Sakh) to the west (the western boundary of the Baikal rift zone – BRZ ) (Fig. 1). One of the main characteristics of the seismic process is seismic activity migration given as sequential activation of seismogenic structures within the seismically active zones and on the global scale [Vikulin et al., 2012; Khain, Khalilov, 2008]. Direct observations show that crust deformation migrates from the Japan-Kuril-Kamchatka subduction zone towards the continent, and the estimated migration rates range from 10 to 140 km per year (e.g. [Ishii et al., 1978; Kasahara, 1979; Harada et al., 2003; Yoshioka et al., 2015]). In the Baikal and Amur regions (107–140°E), the fronts of deformation waves migrate at a rate of 5–20 km per year [Sherman, 2007, 2013]. Considering the order of magnitude, this rate is comparable to the rates of crust deformation migration from the Japan-Kuril-Kamchatka zone (10–100 km per year). Our studies show that the sequential activation of the seismic clusters in the northeastern segment of the Amur plate (Sakh – TanLu – Al-St) occurs at a rate of 1000 km per year [Trofimenko et al., 2015a] (Fig. 1). In the meridional tectonic structures, the shifting chains of maximum seismicity values are sequentially replaced by minimum values (i.e. inversion zones). Based on the spatial cycles with the phase shift of the maximum seismic activity values at the rate of 1000 km per year, it is possible to represent the dynamics of seismicity in the form of a process initiated by long-period stress waves/deformations. According to [Mogi, 1968; Kasahara, 1979; Malamud, Nikolaevskii, 1989; Saprygin et al., 1997; Harada et al., 2003; Bykov, 2005, 2014; Sherman, 2007, 2013, 2014; Milyukov et al., 2013], slow deformation waves of the global and regional scale are generated at the margins of lithospheric plates. Under this concept, the migration rate of seismic activity and the spatial extent of seismic cycles can be identified as the velocity and length of deformation waves. Using the data on seismicity of the most active region of the Baikal rift zone – the northwestern segment of the Amur plate, we have studied the periodic components of seismicity along the entire northern boundary of the Amur plate. An indirect evidence of the existence of deformation waves is the migration of anomalies of geophysical fields and its correlation with the migration of seismic activity. The space-time anomalies of the magnetic and gravity fields were studied in the South Yakutian geodynamic polygon [Trofimenko, 1990; Trofimenko, Grib, 2003, 2016], and the indicators of deformation waves were revealed in the seismic regime and the geophysical fields at the northern margin of the Amur plate. The sequential manifestation of anomalies in the magnetic and gravity fields is associated with the activation of latitudinal tectonic structures. Our estimations show that the geophysical anomalies migrate at different rates, from 100 to 1000 km per year. Based on the results obtained in our study and their comparison with other available data, the dynamics of seismicity along the northern margin of the Amur plate is identified as a wave process.